A low‐background‐intensity focusing small‐angle X‐ray scattering undulator beamline. (1st December 2013) - Kirby, Nigel M.; Mudie, Stephen T.; Hawley, Adrian M.; Cookson, David J.; Mertens, Haydyn D. T.; Cowieson, Nathan; Samardzic‐Boban, Vesna
<x xml:space="preserve">Abstract</x> The SAXS/WAXS beamline at the Australian Synchrotron is an advanced and flexible undulator X‐ray scattering beamline used for small‐ and wide‐angle X‐ray scattering analysis on a wide variety of solids, fluids and surfaces across a diverse range of research and development fields. The beamline has numerous features that minimize the intensity of the instrument background, provide automated stable optics, and allow accurate analysis of very weakly scattering samples. The geometric and intensity requirements of a three‐slit collimation system are described in detail for conventional metal and single‐crystal germanium slits. Straightforward ray tracing and simple linear projections describe the observed direct beam as well as parasitic background scattering geometry of the beamline at its longest camera length, providing a methodology for the design and operation of similar beamlines. As an aid to instrument design, the limit of background intensity determined by the intensity incident on single‐crystal germanium guard slit edges and its q dependence was quantified at 11 keV. Details of the beamline's implementation, underlying optical concept and measured performance are given.